Crop–livestock-integrated farming system: a strategy to achieve synergy between agricultural production, nutritional security, and environmental sustainability - Shanmugam, P. M.; Sangeetha, S. P.; Prabu, P. C.; Varshini, S. V.; Renukadevi, A.; Ravisankar, N.; Parasuraman, P.; Parthipan, T.; Satheeshkumar, N.; Natarajan, S. K.; Gopi, Marappan (Frontiers in Sustainable Food Systems, 2024)
Climate change, nutritional security, land shrinkage and increasing human population are the most concerning factors in agriculture and an further complicated by deteriorating soil health. Among several ways to address these issues, the most prominent and cost-effective means is to adopt Integrated Farming System (IFS). Integrating farming system with livestock enables a way to increase economic yield per unit area per unit time for farmers under small and marginal category. This system effectively utilizes the waste materials by recycling them via linking appropriate components, thereby minimizing the pollution caused to the environment. Further integrating livestock components with crops, production of eggs, meat and milk leads to nutritional security and stable farmer’s income generation. So, there is dire need to develop an eco-friendly, ecologically safe and economically profitable IFS model. Methods: An experiment was conducted to develop crop–livestock based integrated farming system model for the benefit of irrigated upland farmers of semi-arid tropics for increasing productivity, farm income, employment generation and food and nutritional security through efficient utilization of resources in the farming system. Results and discussion: The IFS model with components viz., crop (0.85 ha) + horticulture (0.10 ha) + 2 cattles along with 2 calves in dairy (50 m2) + 12 female goat and one male goat (50 m2) + 150 numbers of poultry birds (50 m2) + vermicompost (50 m2) + kitchen garden (0.02 ha) + boundary planting + supporting activities (0.01 ha) in one- hectare area. The model recorded higher total MEY (162.31 t), gross return ( 6,89,773), net return ( 3,17,765), employment generation (475 man days). Further negative emission of -15118 CO2-e (kg) greenhouse gas was recorded under this model. The study conclusively reveals that integration crop, horticulture, dairy, goat, poultry, vermicompost production, kitchen garden and boundary planting model increases the net returns, B:C ratio besides employment generation, nutritional security and livelihoods of small and marginal farmers.